The Bullseye Principle - Lewis, David; Mills, G. (Ascent Audio, 2018)
The Bullseye Principle is the definitive how-to guide for communicating, collaborating, and executing as a leader in the corporate arena. With these "soft skills" trending above technical knowledge in executive wish lists, this book provides invaluable guidance for new and experienced leaders alike; from the planning stages to the outcome and beyond, the discussion features critical insight and actionable tips based on award-winning methods. Polish your presence, utilize intention, influence emotion, engage workers, build relationships, make connections, and leverage the power of storytelling-it all comes down to technique. The success of any communication rests more on how the information is conveyed than what that information actually is; at every level, in every sphere, effective leaders strive to master key skills that inspire, empower, motivate, and more. This book gives you a solid blueprint for effective communication in nearly any situation, merging the practical and theoretical to help you: - Master the most challenging business interactions - Become more influential as a leader and communicator - Adopt a 3-step methodology to collaborate more effectively - Build your personal brand and executive presence toward sustained success.